ETE 3: reconstruction, analysis, and visualization of phylogenomic data - Huerta-Cepas, Jaime; Serra, François; Bork, Peer (Molecular biology and evolution, 2016)
Abstract. The Environment for Tree Exploration (ETE) is a computational framework that simplifies the reconstruction, analysis, and visualization of phylogene
Gesehen am 05.09.2019